2022
DOI: 10.1111/twec.13339
|View full text |Cite
|
Sign up to set email alerts
|

The proximity‐concentration trade‐off with multi‐product firms: Are exports and FDI complements or substitutes?

Abstract: Standard horizontal foreign direct investment (FDI) models predict substitutability between FDI and exports in light of the proximity‐concentration trade‐off, nonetheless, empirical literature finds, almost invariably, a complementarity effect. We show that given the multi‐product nature of multinational enterprises both effects coexist at the firm‐level, with a substitutability for some products and a complementarity for others, explaining why the empirical substitutability relation has been so scarce even at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Regarding the relationship between exports and FDI, Bricongne et al (2022) showed that horizontal FDI is a substitute for exports while vertical FDI is a complement to exports, indicating that the effects of exports on FDI are mixed. An estimation of Equation (1) with an export variable was performed, and since the export variable was not significant, it was determined that the effects of exports were mixed and was not included in the estimation for this study.…”
Section: Modelmentioning
confidence: 99%
“…Regarding the relationship between exports and FDI, Bricongne et al (2022) showed that horizontal FDI is a substitute for exports while vertical FDI is a complement to exports, indicating that the effects of exports on FDI are mixed. An estimation of Equation (1) with an export variable was performed, and since the export variable was not significant, it was determined that the effects of exports were mixed and was not included in the estimation for this study.…”
Section: Modelmentioning
confidence: 99%
“…All results are available from the authors upon request. 18 For a recent discussion on the complementarity versus substitutability tradeoff between FDI and exports, see Bricongne et al (2023). 19 See https://www.government.nl/documents/directives/2012/04/12/user-guide-on-strategic-goods-and-services for the Government of the Netherlands' official user guide on strategic goods and services, accessed November 15, 2022.…”
Section: Resultsmentioning
confidence: 99%
“… For a recent discussion on the complementarity versus substitutability tradeoff between FDI and exports, see Bricongne et al (2023). …”
mentioning
confidence: 99%
“…Using French firm-level data over 2002 to 2009, Bricongne et al (2023) show that whether FDI and exports are complements or substitutes depends on whether the product belongs to the core competency of the firm and the size of demand in the destination market. The study reports evidence of the substitutability predicted by standard horizontal FDI models, taking place only for the firm’s best-performing products and in high-demand markets.…”
Section: Exports and Fdi: Nature Of Relationshipmentioning
confidence: 99%